Immediate effect of sciatic neurodynamic slider and tensioner technique on hamstring flexibility and postural balance in healthy adults: a randomized control trial - Yogeshwar, Dharmita; Sahoo, Tapaswini (International Journal of Research in Medical Sciences, 2023)
Background: Inadequate hamstring muscle flexibility leads to impaired balance in healthy individuals. So, the present study is conducted to evaluate the immediate effect of neurodynamic slider and tensioner technique on hamstring muscle flexibility and balance in healthy individuals. Method: Total 42 healthy individuals both male and female age between 18-26 with AKE <70 degree participated in the study. 42 individuals were randomly assigned in two groups. Group A received neurodynamic slider technique followed by group B received tensioner technique. AKE angle was immediately examined before and after the intervention to evaluate hamstring flexibility. Results: Results is concluded that both slider and tensioner technique are equally effective to improve hamstring muscle flexibility (p<0.05) and balance in healthy individuals within the group but. As the findings of between the group shows that both the techniques are equally effective not superior on one another (p>0.05). Conclusions: This study concludes that both the neural slider and tensioner techniques were equally effective in immediately increasing the hamstring flexibility and dynamic postural balance in healthy individuals.